Impact of a carbonated beverage on the surface microhardness of three composite resins in – vitro evaluated - Zevallos Rodríguez, Manuel Alfonso (2023)
Objectives: Compare the impact of an aerated beverage on the surface microhardness of three nanofilled composite resins (Filtek Z250 XT, Filtek Z350 XT and Tetric N - Ceram) evaluated in-vitro. Materials and Methods: This study was applied, analytical, experimental and longitudinal. 48 cylinders (16 cylinders per evaluated composite resin) of 6mm x 4mm, were made, which divided into two subgroups of 8 cylinders; and stored in physiological serum. These were submitted to the effect of Coca-Cola for 10 minutes per day and stored in physiological serum until the next immersion (24 hours); for 7 days. Data analysis was performed using Stata ® 12 Software. The ANOVA means test was applied.. Results: Displayed that the Filtek Z250 XT had a higher surface microhardness value, before (72.93 HV ±4.62) and after the erosive challenge (62.65 HV ±3.42); while Tetric N – Ceram was the resin with the lowest microhardness value, such before (41.16 ± 0.72) and after (37.55 ± 1.03) exposure to Coca – Cola. Conclusions: the carbonated drink had impacted in different measures on the surface microhardness of the evaluated composite resins.